P64 Does pain peak at night? The daily rhythm of musculoskeletal searches on the NHS website. (20th April 2020) - Fuggle, Nicholas R; Masefield, Nicola; Dennison, Elaine M; Cooper, Cyrus
Abstract: Background: With the advent of smartphone technology and the constant availability of information on the internet, it is suspected that searches for clinical symptoms or medical conditions could be a real time indication of the timing of these symptoms. Therefore, we aimed to investigate the daily timing of visits to musculoskeletal pages compared to mental health pages on the NHS website (a major source of online health information in the UK). Methods: In collaboration with NHS Digital we acquired 6 months of data on visits to the NHS website and visits to individual webpages relevant to pain management ("Managing chronic pain", "10 ways to ease pain") musculoskeletal conditions (Rheumatoid arthritis, Osteoarthritis, Arthritis"), anatomical pain (Neck, Back, Shoulder, Elbow or Arm, Foot, Hip, Knee, and Hand pain) and an assortment of mental health pages, (Clinical depression, Generalised Anxiety Disorder). In order to adjust for the overall traffic to the NHS website (which peaks strongly at 9-10pm) the mean numbers of webpage visits per hour of the day over the 6 month period were calculated and divided by the mean number of NHS website visits per hour of the day over the 6 month period. Fourier analysis was used to shape appropriate models and assess daily rhythm. Analysis were performed using STATA version 15. Results: There were a total of 400 million visits to the NHS website over the 6-month period of data collection. The overall trends for traffic to the website included a marked peak in visits in the evening at 9-10pm and a distinct trough overnight. Visits to 'pain management' pages peaked at 11-4am, whereas visits to 'musculoskeletal conditions' pages had a bimodal distribution with the largest peak at 6-7am (and a lesser peak at 9-10pm). This bimodal distribution was echoed on the 'anatomical pain' pages with a greater peak at 6-7am and lesser peak at 9-10pm, except for 'neck pain' and 'back pain' which had higher peaks at 9-10pm and lesser peak at 6-7am. In comparison, visits to 'mental health' pages peaked clearly at 12-1am. Conclusion: Through this investigation of visits to the NHS website we saw clear differences in the distribution of visits relating to 'musculoskeletal conditions', 'anatomical pain' and 'pain management'. These profiles differed substantially to the distribution of 'mental health' page visits. It is interesting that searches for pain management (including the page "10 ways to ease pain" which is the top NHS webpage listed on Google when searching the word "pain") peaked overnight between 11-4am, as this replicates our previous finding from Google search data. These findings provide an insight into the circadian rhythm of interactions with online health data and may even hint at patterns of symptom experience over a 24-hour period. Disclosures: N.R. Fuggle None. N. Masefield None. E.M. Dennison None. C. Cooper None.